Pengaruh Investasi Dan Ekspor Terhadap Pertumbuhan Ekonomi Di Sumatera Barat - Oktaviani, Nichy; Pratama , Marshal Imar; Rahayu, Sari; Rahim, Anwar (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This research aims to determine the influence of investment and exports in West Sumatra. This research was motivated by the lack of investment by the community and the lack of community exports so that economic growth in West Sumatra was hampered. This research uses a quantitative type of research using secondary data. This research carries out classical assumption tests, hypothesis testing using SPSS.Looking at the results of the tests that have been carried out proves that investment has no significant effect on economic growth, while the export variable has a significant effect on economic growth. The results of simultaneous tests of investment and exports have a significant effect on economic growth with a significant value of 0.001 < 0.05. This shows that investment and exports can predict information about economic growth by 0.501 or 50.1%, while the remaining 0.499 or 49.9% is influenced by other factors not included in this research.